EXPERIMENTAL STUDY ON THE OPTIMUM CONTENT OF SILICA FUME ON HIGH STRENGTH CONCRETE MIXTURES - Samuel Sampar, Edwin Geritei (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The results of an experimental study on the optimum content of silica fume on high strength concrete (HSC) mixtures are presented. The study is mainly to investigate the influence of the content of silica fume on the compressive strength development of HSC. The experimental study was focused on the HSC mixtures having three different water-binder ratios (w/b) of 0.35. 0.40, and 0.45 with a total binder of 500 kg/m3. The percentages of silica fume used to replace the cement content were 0%, 10%. 15%. and 20% from the total binder content. A series of pycnometer and specific gravity test was performed to determine the specific gravity of the materials used. Mortar flow tests were performed to evaluate the dosage of superplastisizer (SP) to be used for HSC mixtures. The compressive strength was determined at 28 days by conducting the cömpression tests on cubes (100 mm x 100 nun x I00mm) and cylinder (100 mm x 200 mm) specimens. The results of the experimental investigation show that the optimum content of silica fume on USC mixtures to replace cement content was 15% from the total hinder.